"Teologi" Petani: Respon Masyarakat Petani terhadap Islam Murni - Abdul Munir Mulkhan (Unisia, 2000)
The dynamic development of Islam, especially in the country side farm-are, describes the interaction between the pure Islam—symbolizedby Muhammadiyah —and the farmer tradition. The tradition offarmer religiosity is oftenly connected with superstition, bid'ah and kurafaat. This book is based on the writer's research that shows the sociological description on the aculturation the meeting of both traditions and on the role of village leaders in East-Java. The most important finding is this research is thattheincreasing number of Muhammadiyah followers in the farming - areas is notmainly because of the success oftradition purifying but it is merely supported by some certain social situations.